The Administrative Prevalence of Multiple Sclerosis in Greece on the Basis of a Nationwide Prescription Database - Bakirtzis, Christos; Grigoriadou, Eleni; Boziki, Marina Kleopatra; Kesidou, Evangelia; Siafis, Spyridon; Moysiadis, Theodoros; Tsakona, Dimitra; Thireos, Eleftherios; Nikolaidis, Ioannis; Pourzitaki, Chrysa; Kouvelas, Dimitrios; Papazisis, Georgios; et al. (Frontiers in Neurology, 2020)
Objective: To estimate current prevalence of multiple sclerosis (MS) in Greece using administrative data from the nationwide medicine prescription database. Methods: Prescription records of a 24-month period (June 2017 – May 2019) were analyzed in order to identify cases of MS. Sex, age and place of residence were recorded for each identified case. Prevalence of MS was calculated based on the updated records of the Greek population according to Hellenic Statistical Authority. Results: The 2-year cumulative period prevalence of MS was estimated to 197.8 per 100,000 (95% CI 197.6 – 198.0). In total, 21,218 patients (65.8 % female) were identified. During this period, the prevalence of MS was 138.7 per 100,000 (95% CI 138.4 – 139.0) in men and 253.6 per 100,000 (95% CI 253.3 – 254.1) in women. Prevalence was higher in the 45-49 age group in both sexes. Analysis of the place of residence, revealed higher prevalence in Attica region and Western Greece while lower prevalence was observed in Northern Greece. No north - south latitude gradient was detected. Point prevalence on 1st January 2019 was calculated to 188.9 per 100,000 (95% CI 188.7-189.1). Regarding treatment, 73.1% of the identified cases received at least once a Disease Modifying Drug. Conclusions: According to this national-level study conducted in Greece, estimated prevalence of MS was found to be similar to those of other European countries. Heterogeneity of MS prevalence across the country was observed and needs further investigation.